CONGENITAL HEART DISEASE IN CHILDREN AND ADULTSPrevention of infectious complications after heart surgery in children: procalcitonin-guided strategy - Popov, Dmitry; Yaroustovsky, Michail; Lobacheva, Galina (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction: Infectious complications remain a significant problem of modern cardiac surgery. New prevention strategies, based on the pathogenesis of such complications occurring after cardiopulmonary bypass (CPB) procedures, should be evaluated. Aim of the study: To evaluate the effectiveness of a procalcitonin (PCT)-guided strategy involving the use of IgM-enriched intravenous immunoglobulins (IVIGs) in children with congenital heart disease with systemic inflammation during the early postoperative period. Material and methods: Sixty consecutive patients aged 25 (21-30) months who underwent cardiac surgery with CPB and had blood PCT levels > 2 ng/mL on the 1st postoperative day were enrolled in this single-center prospective randomized clinical trial. The patients were randomized into two groups, comparable in terms of the severity of their initial condition, age, and CPB time. IgM-enriched IVIGs (Pentaglobin, Biotest Pharma GmbH, Germany) were administered during the first 3 postoperative days (5 mL/kg each day) in the study group (n = 30) in addition to the standard treatment, which was also provided to the control group (n = 30). The data are presented as medians with 25-75th percentiles; they were compared by the Mann-Whitney U-test, and p values of < 0.05 were considered as statistically significant. Results: Postoperatively, 1/30 (3.3%) patients in the study group and 8/30 (26.7%) in the control group suffered from infectious complications (study group: urinary tract infection [UTI] – 1; control group: pneumonia – 4, pneumonia and sepsis – 2, peritonitis with multiorgan failure – 1, UTI – 1), p = 0.03. The length of hospital stay in the study group was shorter than in the control group: 19 (16-23) days vs. 24 (19-29) days, p = 0.02, as was the length of intensive care unit (ICU) stay: 3 (2-4) days vs. 4 (2-8) days, p = 0.03. Conclusions : High PCT levels on the 1st postoperative day are associated with an increased risk of infectious complications after cardiac surgery. Early administration of IgM-enriched IVIGs can prevent the development of infectious complications.